An unusual presentation of mycotic aneurysm of popliteal artery and the challenges faced: a case report - Kuruvilla, Obed Manuel; Narayanapanicker, Arun; Antony, Anu Tresa (International Surgery Journal, 2021)
Mycotic aneurysm of popliteal artery is a very rare condition, most commonly caused by gram positive organisms. This term was coined by William Osler describing aneurysms associated with bacterial endocarditis. Though cases of peripheral vessel mycotic aneurysm are very rare, it is a dangerous condition as it can go for rupture/ thrombosis. The treatment of choice is resection and revascularization, preferably by using autologous vein graft along with antibiotics. A 35-year-old female who presented with features of cerebrovascular accident, during the course of stay was diagnosed to have mycotic aneurysm of the left popliteal artery. We describe the clinical course, investigation findings and challenges faced in management of the case.